A review of ns-pulsed Raman lasers based on diamond crystal - Liu, Yuxuan; You, Wei; Zhu, Chengjie; Li, Muye; Sun, Yuxiang; Yin, Xiongfei; Chen, Dijun; Feng, Yan; Chen, Weibiao; Yang, Xuezong (Frontiers in Physics, 2022)
High-power ns-pulsed lasers have been widely used in many significant applications, including laser radar, remote-sensing, biomedicine, industrial process, and military defense. Stimulated Raman scattering (SRS) provides an efficient method for extending the wavelengths of laser radiation. Due to the excellent thermal conductivity, high damage threshold, and high gain coefficient, diamond crystal is considered the most potential SRS material to address laser output in specific wavelength regions with high power, high beam quality, and high conversion efficiency. This paper reviews the advances of ns-pulsed crystalline Raman lasers and particularly emphasizes the latest progress of ns-pulsed diamond Raman lasers (DRLs) in the past decade. DRL has demonstrated a maximum peak power of 1.2 MW at 1240 nm with a pulse duration of 8 ns. It can also generate high-energy ns pulses featuring Fourier-limited spectral linewidth. The superior optical characteristics and the mature technology of synthetic diamond crystal will make DRL a promising technique to achieve higher performance ns laser pulses.